Monitoring of four major lepidopteran pests in Korean cornfields and management of Helicoverpa armigera - Kim, Juil; Kwon, Min; Park, Ki Jin; Maharjanm, Rameswor (Entomological research, 2018)
Lepidopterans such as Helicoverpa armigera are emerging pests of corn in Korea, causing huge yield losses and deteriorating the quality of the corn crop. We monitored four major lepidopteran pests in major corn growing areas of Korea by employing sex pheromone traps from 2012 to 2015 to understand population dynamics. H. armigera , Ostrinia furnacalis , Spodoptera litura , Spodoptera exigua and Mythimna separata were collected from April to October. Among these species, H. armigera was found to be the main pest based on crop damage intensity (80–90% of the total damage). H. armigera was generally observed during the earing stage of corn and would migrate to other fields during September to October for overwintering. We also tested select insecticides against larvae of H. armigera in the laboratory. The most effective insecticide was indoxacarb, which was applied at specific times to manage H. armigera in cornfields. Optimal timing of spraying was estimated at about 70 days after planting (earing season) to control for H. armigera . Additionally, two species of parasitoid ( Therion circumflexum and Ophioninae sp .) were identified from H. armigera . However, more extensive surveys are needed to organize a control program based on natural enemies.